1792 N.Y. Laws 191 - (:unkn) unknown (My University, 1792)
Prohibited storing of gun powder beyond twenty-eight pounds in weight in one location. Violators fined fifty pounds for every "hundred weight" of powder overstocked. Note: The law was passed in 1788, not 1792.
Keywords: GUNPOWDER - STORAGE